Capsaicin for post-surgical neuropathic peripheral pain – calculation of allodynia area - Ferreira, D. (2016)
Poster apresentado no Congresso O Norte da Anestesia, 19-21 Novembro 2015, Hotel Ipanema Park, Porto, Portugal.